Sex-Specific Behavioral Response to Early Adolescent Stress in the Genetically More Stress-Reactive Wistar Kyoto More Immobile, and Its Nearly Isogenic Wistar Kyoto Less Immobile Control Strain - Kim, Sarah; Gacek, Stephanie A.; Mocchi, Madaline M.; Redei, Eva E. (Frontiers in Behavioral Neuroscience, 2021)
Genetic predisposition and environmental stress are known etiologies of stress-related psychiatric disorders. Environmental stress during adolescence is assumed to be particularly detrimental for adult affective behaviors. To investigate how genetic stress-reactivity differences modify the effects of stress during adolescence on adult affective behaviors we employed two inbred strains with differing stress reactivity. The Wistar Kyoto More Immobile (WMI) rat strain show increased stress-reactivity and despair-like behaviors as well as passive coping compared to the nearly isogenic control strain, the Wistar Kyoto Less Immobile (WLI). Males and females of these strains were exposed to contextual fear conditioning (CFC) during early adolescence (EA), between 32-34 postnatal days (PND), and were tested for the consequences of this mild EA stress in adulthood. Early adolescent stress significantly decreased anxiety-like behavior, measured in the open field test (OFT) and increased social interaction and recognition in adult males of both strains compared to controls. In contrast, no significant effects of EA stress were observed in adult females in these behaviors. Both males and females of the genetically less stress-reactive WLI strain showed significantly increased immobility in the forced swim test (FST) after EA stress compared to controls. In contrast, immobility was significantly attenuated by EA stress in adult WMI females compared to controls. Transcriptomic changes of the glucocorticoid receptor (Nr3c1, GR) and the brain-derived neurotrophic factor (Bdnf) illuminate primarily strain and stress-dependent changes, respectively, in the prefrontal cortex and hippocampus of adults. These results suggest that contrary to expectations, limited adolescent stress is beneficial to males thru decreasing anxiety and enhancing social behaviors, and to the stress more-reactive WMI females by way of decreasing passive coping.